Nano laminated film material-based antireflection film and design method thereof

By introducing a gradient refractive index interface layer model into the nano-laminated film materials, the problems of large refractive index changes with thickness and sub-layer diffusion in nano-laminated film materials are solved, and the optical performance and accuracy of the anti-reflective film are improved.

CN119717082AActive Publication Date: 2025-03-28SHANGHAI INST OF OPTICS & FINE MECHANICS CHINESE ACAD OF SCI

Patent Information

Application Number
CN202311278389.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

When the thickness of the neutron layer material is thinner, the refractive index varies greatly with the thickness, and the diffusion between the sub-layer materials affects the refractive index and thickness, resulting in a deviation from the spectral performance of the actual film prepared.

Method used

A gradient refractive index interface layer model is introduced into nano-laminated film materials. By adjusting the thickness and refractive index of material A and material B sublayers, combining the characteristics of the interface diffusion layer, the refractive index and thickness of the film are corrected to reduce the error between the experimental spectrum and the theoretical spectrum.

Benefits of technology

It effectively improves the optical performance of the anti-reflective film, reduces the error between the experimental spectrum and the theoretical spectrum, and is suitable for film designs with other spectral properties that are sensitive to the refractive index and thickness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119717082A_ABST
    Figure CN119717082A_ABST
Patent Text Reader

Abstract

The invention discloses an antireflection film based on a nano laminated film material and a design method of the antireflection film. The method comprises the following steps: obtaining functions of refractive indexes of a material A and a material B and thickness and wavelength of a film layer; the refractive index and the thickness of each layer of the antireflection film are corrected based on an interface layer model between two material sub-layers in the nanometer laminated film material; and adopting the corrected refractive index and thickness to design the structure of the thin film, and carrying out thin film preparation and testing. According to the invention, film system design is carried out based on a graded-index interface layer model between two material sub-layers in a nano laminated film material, so that the error between an experimental spectrum and a theoretical spectrum is effectively reduced, and the spectral performance of the antireflection film is improved; the method is suitable for the design of other films with spectral properties sensitive to the refractive index and thickness of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a design method for an anti-reflection film, in particular to an anti-reflection film based on a nano-laminated film material and a design method thereof. Background Art

[0002] Nano-laminated thin film materials are thin film materials formed by alternating deposition of two sub-layer materials with thicknesses ranging from several nanometers to tens of nanometers. Nano-laminated thin film materials have the advantage that the refractive index and optical band gap can be arbitrarily tuned within a certain range, and are suitable for a variety of thin film deposition technologies such as atomic layer deposition, electron beam evaporation, ion beam sputtering, and magnetron sputtering, which provide great flexibility for the design and preparation of optical thin films. They are widely used in the design and preparation of various types of thin films such as anti-reflection and high reflection. However, when the thickness of the sub-layer material in the nano-laminated thin film material is thin, its refractive index varies greatly with thickness; in addition, the diffusion between the two sub-layer materials will also affect the refractive index and thickness of the sub-layer material. The above two factors will cause the spectral performance of the actual prepared film to deviate from the designed spectral performance, especially for thin film structures whose spectral performance is sensitive to the refractive index and thickness of the material. The deviation between the prepared and designed spectral performance is even greater, and even the spectral performance of the actual preparation cannot meet the index requirements. Summary of the invention

[0003] The technical problem to be solved by the present invention is to overcome the shortcomings of the above-mentioned prior art and provide an anti-reflection film based on a nano-laminated thin film material and a design method thereof. The method introduces a gradient refractive index interface layer model between two material sub-layers in the nano-laminated thin film material, effectively reducing the error between the experimental spectrum and the theoretical spectrum, and improving the optical performance of the anti-reflection film; the method is suitable for the design of other films whose spectral performance is sensitive to the refractive index and thickness of the material.

[0004] The technical solution of the present invention is as follows:

[0005] On the one hand, the present invention provides an anti-reflection film based on a nano-laminated thin film material, characterized in that the anti-reflection film is obtained by randomly and alternately depositing a single-layer film of material A, a single-layer film of material B, and a nano-laminated thin film material C formed by alternating sub-layers of material A and sub-layers of material B;

[0006] The thickness of the sublayer film of material A in the nano-laminated film material C is d A , the refractive index at wavelength λ is n A (λ); the thickness of the sublayer of material B in the nano-laminated film material C is d B , the refractive index at wavelength λ is n B (λ); the thickness of the interface diffusion layer between the material A sublayer and the material B sublayer is d I , the nano-laminated thin film material C satisfies the following interface layer model conditions:

[0007] When A <d I , then n M (λ)=ρ M ×n B (λ)+(1-ρ M )×n A (λ), where n M (λ) is the refractive index at the middle point M of the diffusion layer, ρ M is the proportion of material B at the middle point M of the diffusion layer, The refractive index n of the interface diffusion layer I (λ) takes the middle point M of the diffusion layer as the extreme point in n M (λ) and n B (λ) linear gradient;

[0008] When A >d I And d B >d I , the refractive index of the interface diffusion layer n I (λ) in n A (λ) and n B (λ) linear gradient;

[0009] When B <d I , then n M (λ)=ρ M ×n B (λ)+(1-ρ M )×n A (λ), Refractive index of interface diffusion layer n I (λ) takes the middle point M of the diffusion layer as the extreme point in n M (λ) and n A (λ) linear gradient.

[0010] On the other hand, the present invention also provides a method for designing an anti-reflection film based on a nano-laminated film material, wherein the method comprises the following steps:

[0011] Step 1: Obtain the refractive index of material A and material B as a function of film thickness and wavelength n A (d A ,λ)、n B (d B ,λ);

[0012] a) preparing a single-layer film of material A with different thicknesses in group N1 and a single-layer film of material B with different thicknesses in group N2, wherein the thickness ranges from 0 to 20 nm; N1≥4, N2≥4;

[0013] b) Transmission electron microscopy was used to characterize the single-layer film thickness of material A and material B. A and d B , perform ellipsometric fitting or transmission spectrum fitting on the single-layer film to obtain the function n of the refractive index of material A and material B and the film thickness A (d A ,λ)、n B (d B ,λ);

[0014] Step 2: Obtain the thickness d of the interface diffusion layer in the nano-laminated thin film material C I The thickness of the sub-layer film of material A is d A and the thickness of the material B sublayer film d B relationship;

[0015] a) preparing group N3 of nano-laminated thin film material C formed by alternating deposition of material A sublayers and material B sublayers with different thickness ratios, with a constant periodic thickness ranging from 15 to 40 nm; N3 ≥ 4;

[0016] b) Transmission electron microscopy was used to characterize the thickness d of the material A sublayer and the material B sublayer in the nano-laminated thin film material C. A and d B The thickness d of the interface diffusion layer between the material A sublayer and the material B sublayer in the nano-laminated thin film material C is obtained by using an energy spectrometer. I , and obtain the thickness of the interface diffusion layer d I The relationship with the thickness of the sublayer.

[0017] Step 3: Use the interface layer model to correct the refraction and thickness of each layer in the anti-reflection film, design the film structure, and carry out film preparation and testing.

[0018] Furthermore, material A includes but is not limited to HfO2 or Ta2O5, and material B includes but is not limited to SiO2 or Al2O3.

[0019] Furthermore, the preparation adopts one of electron beam evaporation deposition, atomic layer deposition or sputtering deposition.

[0020] Furthermore, the film structure of the nano-laminated material C is Sub / (BA) m / Air, m≥4, Sub is the substrate, and Air is air.

[0021] Technical effects of the present invention:

[0022] 1. The method of the present invention introduces a model of a gradient refractive index interface layer between two material sub-layers in a nano-laminated thin film material, which can effectively reduce the error between the experimental spectrum and the theoretical spectrum and improve the spectral performance of the anti-reflection film.

[0023] 2. The method of the present invention is applicable to the design of other thin films whose spectral properties are sensitive to the refractive index and thickness of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 .Refractive index curves of HfO2 material (left) and SiO2 material (right) in Example 1 of the present invention.

[0025] Figure 2 .The relationship between the refractive index of HfO2 material (left) and SiO2 material (right) at 510nm and the film thickness and the fitting curve in Example 1 of the present invention.

[0026] Figure 3 . Schematic diagram of the refractive index profile at a wavelength of 510nm obtained based on the interface layer model of the SiO2 / HfO2 nano-laminated film in Example 1 of the present invention.

[0027] Figure 4 .The measured spectrum and designed spectrum of the anti-reflection film in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] Embodiment 1:

[0029] Taking materials HfO2 and SiO2 as examples, under normal incidence conditions, the reference wavelength is 510nm, and the average reflectivity in the wavelength range of 500nm to 900nm is set as the target to be less than 1%. The anti-reflection film based on nano-laminated thin film materials and the design method thereof of the present invention are described, and the specific steps are as follows.

[0030] Step 1. Atomic layer deposition was used to prepare 4 groups of HfO2 single-layer films with different thicknesses on a silicon substrate with a diameter of 25.4 mm and a fused quartz substrate with a diameter of 30 mm; 6 groups of SiO2 single-layer films with different thicknesses; and 9 groups of SiO2 / HfO2 nano-laminated films with different sub-layer thickness ratios. The film structure was Sub / (SiO2 / HfO2) 4 / Air, Sub base, Air means air.

[0031] Step 2. Use transmission electron microscopy to characterize the actual thickness of 4 groups of HfO2 monolayer films and 6 groups of SiO2 monolayer films prepared on silicon substrates and The transmission spectrum of the sample prepared on the fused silica substrate was measured by a spectrophotometer, and the refractive index was calculated; the refractive index function of HfO2 material and SiO2 material was obtained. like Figure 1 . Figure 2 The relationship between the refractive index of HfO2 and SiO2 materials and the actual film thickness at a wavelength of 510nm and the fitting curve are given. Figure 1 and Figure 2It can be seen that the refractive index of HfO2 material is greatly affected by the film thickness; the refractive index of SiO2 material is less affected by the film thickness. In this embodiment, the refractive index of SiO2 material at a wavelength of 510 nm is set to a constant of 1.455.

[0032] Step 3. Use an energy spectrometer to characterize and obtain the thickness of the interface diffusion layer in the SiO2 / HfO2 nano-laminated film, as shown in Table 1. It can be obtained that when the thickness of the sub-layers is relatively thick, the thickness of the interface diffusion layer tends to be stable.

[0033] Table 1. Sublayer thickness and interface diffusion in nanolaminated thin film materials

[0034]

[0035] The gradient refractive index interface layer model is established at a reference wavelength of 510nm as follows:

[0036] (1) Thickness of HfO2 sublayer in samples 1 and 2 Less than the thickness of the interface diffusion layer d I , the refractive index n of the middle point M of the diffusion layer M Calculated by formula (1) and (2), they are 1.572 and 1.643 respectively. The refractive index of HfO2 sublayer and SiO2 sublayer and According to step 2, the refractive index of the HfO2 sublayer in samples 1 and 2 is 1.734 and 1.759 respectively, and the refractive index of the SiO2 sublayer is 1.455.

[0037]

[0038]

[0039] Among them, ρ M is the proportion of material SiO2 at the middle point M of the diffusion layer.

[0040] (2) Thickness of HfO2 sublayer and SiO2 sublayer in samples 3-6 and Both are greater than the thickness of the interface diffusion layer d I , the refractive index of the HfO2 sublayer and the SiO2 sublayer and All are obtained according to step 2, as shown in the following table.

[0041] Table 2. Refractive index of HfO2 sublayer and SiO2 sublayer in samples 3-6

[0042]

[0043] (3) SiO2 sublayer thickness in samples 7-9 Less than the thickness of the interface diffusion layer dI , the refractive index n of the middle point M of the diffusion layer M Calculated by formulas (3) and (4), they are 1.467, 1.575 and 1.648 respectively. The refractive index of the HfO2 sublayer and the SiO2 sublayer and According to step 2, the refractive index of the HfO2 sublayer in samples 7-9 is 1.845, 1.856 and 1.866, respectively, and the refractive index of the SiO2 sublayer is 1.455.

[0044]

[0045]

[0046] Among them, ρ M is the proportion of material SiO2 at the middle point M of the diffusion layer.

[0047] Figure 3 Schematic diagram of the refractive index profile at a wavelength of 510 nm obtained according to the above model.

[0048] Step 4. Design an anti-reflection film based on nano-laminated film material with a reference wavelength of 510nm. The film structure is Sub / M1LM2HL / Air, where Sub is the substrate, Air is air, and M1 represents the structure (L N1 H N1 ) 4 Nano-laminated, M2 represents the structure (L N2 H N2 ) 4 of nano-laminates.

[0049] According to the preliminary design of the film thickness, the thickness of the interface layer is determined to be 6nm according to step 3. First, the film thickness of each layer in the anti-reflection film is corrected, and then the refractive index of each layer is corrected according to the corrected film thickness. Specific design information is shown in Table 2.

[0050] Table 2 Refractive index and thickness information of each layer of the anti-reflection film in the embodiment

[0051]

[0052] Step 5. Prepare the designed anti-reflection film on a K9 substrate with a diameter of 30 mm using atomic layer deposition technology.

[0053] The prepared anti-reflection film was subjected to spectral testing using a spectrophotometer, and within the wavelength range of 500 nm to 900 nm, the average reflectivity was measured to be 0.61%. Figure 4 Comparison of the measured spectrum with the traditional design spectrum and the modified design spectrum. It can be seen that after the refractive index and thickness correction, the error between the measured spectrum and the designed spectrum is significantly reduced.

[0054] Other embodiments:

[0055] Example Material A Material B Material C Average reflectivity from 500nm to 900nm 2 <![CDATA[HfO2]]> <![CDATA[Al2O3]]> <![CDATA[HfO2 / Al2O3 nano-laminate]]> ≤1% 3 <![CDATA[Ta2O5]]> <![CDATA[SiO2]]> <![CDATA[Ta2O5 / SiO2 nano - laminate]]> ≤2% 4 <![CDATA[Ta2O5]]> <![CDATA[Al2O3]]> <![CDATA[Ta2O5 / Al2O3 nano-laminate]]> ≤2%

Claims

1. An anti-reflection film based on nano-laminated film material, characterized in that: The anti-reflection film is obtained by randomly and alternately depositing a single-layer film of material A, a single-layer film of material B, and a nano-laminated film material C formed by alternating sub-layers of material A and sub-layers of material B; The thickness of the sublayer film of material A in the nano-laminated film material C is d A , the refractive index at wavelength λ is n A (λ); the thickness of the sublayer of material B in the nano-laminated film material C is d B , the refractive index at wavelength λ is n B (λ); the thickness of the interface diffusion layer between the material A sublayer and the material B sublayer is d I , the nano-laminated thin film material C satisfies the following interface layer model conditions: When A <d I , then n M (λ)=ρ M ×n B (λ)+(1-ρ M )×n A (λ), where n M (λ) is the refractive index at the middle point M of the diffusion layer, ρ M is the proportion of material B at the middle point M of the diffusion layer, The refractive index n of the interface diffusion layer I (λ) takes the middle point M of the diffusion layer as the extreme point in n M (λ) and n B (λ) linear gradient; When A >d I And d B >d I , the refractive index of the interface diffusion layer n I (λ) in n A (λ) and n B (λ) linear gradient; When B <d I , then n M (λ)=ρ M ×n B (λ)+(1-ρ M )×n A (λ), Refractive index of interface diffusion layer n I (λ) takes the middle point M of the diffusion layer as the extreme point in n M (λ) and n A (λ) linear gradient.

2. A method for designing an anti-reflection film based on a nano-laminated film material, characterized in that: The design method comprises the following steps: Step 1: Obtain the refractive index of material A and material B as a function of film thickness and wavelength n A (d A ,λ)、n B (d B ,λ); a) preparing a single-layer film of material A with different thicknesses in group N1 and a single-layer film of material B with different thicknesses in group N2, The thickness range is 0-20 nm; N1≥4, N2≥4; b) Transmission electron microscopy was used to characterize the single-layer film thickness of material A and material B. A and d B , Perform ellipsometric fitting or transmission spectrum fitting on the single-layer film to obtain the function n of the refractive index of material A and material B and the film thickness A (d A ,λ)、n B (d B ,λ); Step 2: Obtain the thickness d of the interface diffusion layer in the nano-laminated thin film material C I The thickness of the sub-layer film of material A is d A and the thickness of the material B sublayer film d B relationship; a) preparing group N3 of nano-laminated thin film material C formed by alternating deposition of material A sublayers and material B sublayers with different thickness ratios, with a constant periodic thickness ranging from 15 to 40 nm; N3 ≥ 4; b) Transmission electron microscopy was used to characterize the thickness d of the material A sublayer and the material B sublayer in the nano-laminated thin film material C. A and d B The thickness d of the interface diffusion layer between the material A sublayer and the material B sublayer in the nano-laminated thin film material C is obtained by using an energy spectrometer. I , and obtain the thickness of the interface diffusion layer d I The relationship with the thickness of the sublayer. Step 3: Use the interface layer model to correct the refraction and thickness of each layer in the anti-reflection film, design the film structure, and carry out film preparation and testing.

3. The method for designing an anti-reflection film based on nano-laminated film materials according to claim 2, characterized in that: Material A includes but is not limited to HfO2 or Ta2O5, and material B includes but is not limited to SiO2 or Al2O3.

4. The method for designing an anti-reflection film based on nano-laminated film materials according to claim 2, characterized in that: In the step 1, the preparation is carried out by electron beam evaporation deposition, atomic layer deposition or sputtering deposition.

5. The method for designing an anti-reflection film based on nano-laminated film materials according to claim 2, characterized in that: In step 1, the film structure of the nano-laminated material C is Sub / (BA) m / Air, m≥4, Sub is the substrate, and Air is air.

Citation Information

Patent Citations

  • Film system for correcting thin film high and low refraction index material relative thickness ratio

    CN106066498A

  • Ultralow residual reflectance ZnS substrate long wave antireflection film

    CN106443841A

  • Method for improving laser-damaged threshold of HfO2 / Al2O3 / SiO2 ultraviolet reflective thin film based on gradational contact nano-thin layer technology

    CN110441845A

  • Antireflective film, optical member, and method for producing antireflective film

    WO2019187417A1

Cited By

  • Single-cycle SiO2 interface modification-based Al2O3 / HfO2 nano laminated film defect suppression method

    CN121519026A